2012
DOI: 10.3390/en5082874
|View full text |Cite
|
Sign up to set email alerts
|

Are the Greenhouse Gas Implications of New Residential Developments Understood Wrongly?

Abstract: Built environment carbon reduction strategies materialize predominantly in city-level greenhouse gas (GHG) management, where new residential development appears as one of the key instruments. However, city-level assessments are often incapable of producing data at a community or neighborhood level and thus they may heavily underestimate the emissions from new construction. This paper explores the implications of low-energy residential construction as an instrument of climate change mitigation in the built envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The carbon Int J Disaster Risk Sci 227 footprint of several wood-framed buildings have been calculated and analyzed according to ISO and EN standards (Kuittinen et al 2013). Environmental impacts on residential neighborhoods have also been analyzed in detail, by using, for example, economic input-output assessment methods (Heinonen et al 2012). Despite the great number of carbon footprint studies that have been performed and normative standards that have been developed, there is not adequate scientific information about the environmental impacts or GHG emissions of humanitarian construction.…”
Section: Focus On the Construction Sectormentioning
confidence: 99%
“…The carbon Int J Disaster Risk Sci 227 footprint of several wood-framed buildings have been calculated and analyzed according to ISO and EN standards (Kuittinen et al 2013). Environmental impacts on residential neighborhoods have also been analyzed in detail, by using, for example, economic input-output assessment methods (Heinonen et al 2012). Despite the great number of carbon footprint studies that have been performed and normative standards that have been developed, there is not adequate scientific information about the environmental impacts or GHG emissions of humanitarian construction.…”
Section: Focus On the Construction Sectormentioning
confidence: 99%
“…In addition to the computational and storage limitations for the airflow modeling around buildings and their implications of the energy use patterns of buildings in urban neighborhoods, there are inherent restrictions with the availability of reliable and public building energy data for the validation of the simulated building energy consumption in a large scale for a cluster of buildings [12]. In the U.S., recent city building benchmarking data and data from the Commercial Building Energy Consumption Survey (CBECS) are two major, public, and large-scale building energy consumption data sources [13].…”
Section: University Campuses As Urban Neighborhoodsmentioning
confidence: 99%
“…The coupling requires careful consideration of the spatial and temporal time steps for the two directional dynamic exchange of the data from different modeling approaches. In the next couple of decades, it is expected that the impacts of urban neighborhoods on the buildings and associated modeling approaches need to be resolved within 1 km [11], suggesting that an integrated modeling simulation of the built environment should start from the neighborhood scale rather than the a city scale.In addition to the computational and storage limitations for the airflow modeling around buildings and their implications of the energy use patterns of buildings in urban neighborhoods, there are inherent restrictions with the availability of reliable and public building energy data for the validation of the simulated building energy consumption in a large scale for a cluster of buildings [12]. In the U.S., recent city building benchmarking data and data from the Commercial Building Energy Consumption Survey (CBECS) are two major, public, and large-scale building energy consumption data sources [13].…”
mentioning
confidence: 99%
“…In another study [28], the CO2 equivalent emissions originating from building materials and products is between 2.4 to 3.1 times higher compared to CO2-equivalent emissions originating from building energy use during operation when the building facade was non-wooden and the service life was 50 years. A different study [29] that employed a hybrid life-cycle assessment (LCA) approach demonstrated that when the temporal allocation of emissions from the construction and use phases is taken into account, construction-phase emissions play a central role in finding effective GHG mitigation strategies-even when the emissions from all consumption activities during the use phase are included in the assessment.…”
Section: Introductionmentioning
confidence: 99%